Why sub-Saharan Africa lags in electronic health record adoption and possible strategies to increase its adoption in this region - Odekunle, Florence Femi; Odekunle, Raphael Oluseun; Shankar, Srinivasan (International Journal of Health Sciences, 2017)
Poor health information system has been identified as a major challenge in the healthcare system in many developing countries including sub-Saharan African countries. Electronic health record (EHR) has been shown as an important tool to improve access to patient information with attendance improved quality of care. However, EHR has not been widely implemented/adopted in sub-Saharan Africa. This study sought to identify factors that affect the adoption of an EHR in sub-Saharan Africa and strategies to improve its adoption in this region. A comprehensive literature search was conducted on three electronic databases: PubMed, Medline, and Google Scholar. Articles of interest were those published in English that contained information on factors that limit the adoption of an EHR as well as strategies that improve its adoption in sub-Saharan African countries. The available evidence indicated that there were many factors that hindered the widespread adoption of an EHR in sub-Saharan Africa. These were high costs of procurement and maintenance of the EHR system, lack of financial incentives and priorities, poor electricity supply and internet connectivity, and primary user’s limited computer skills. However, strategies such as implementation planning, financial supports, appropriate EHR system selection, training of primary users, and the adoption of the phased implementation process have been identified to facilitate the use of an EHR. Wide adoption of an EHR in sub-Saharan Africa region requires a lot more effort than what is assumed because of the current poor level of technological development, lack of required computer skills, and limited resources.